Aproveitamento de águas pluviais em estabelecimentos hospitalares no contexto da conservação da água: estudo do caso no Hospital Universitário da UFSCar, São Carlos – SP - Gaitán, Maria Camila Perdomo (Universidade Federal de São Carlos, 2018)
The use of rainwater is being stimulated by different purposes: as an alternative source of supply in regions subject to the lack of water, as an instrument to raise awareness of the efficient use of water and will constitute an important tool in the management of water resources in the cities. The implementation of exploitation rainwater systems in buildings with significant water consumption, such as health centers, can bring great benefits, as well as economic for users and environmental for environment. Since water represents an essential element in the development of the activities that occur in these buildings, and they require a significant daily amount, for their different purpose, correspond largely to uses that not require special quality characteristics. Taking account all the above the purpose of this article is to evaluate the viability of implementing a rainwater harvesting system as an alternative to water supply in a health center, having as an object of study the University Hospital of the Federal University of São Carlos - SP (HU).This was determined by the conception of a replicable scientific methodology based on technical, financial and environmental sustainability criteria; which is constituted main aspects, as the classification of water demand in relation to it ends uses, the potential of water savings through different scenarios of supply and demand, the analysis of the main infrastructure requirements for the implementation of systems, and so the financial viability of the project can be determined. Based on the available rainwater and the water consumption of the current building supply, the monthly supply-demand was determined for three consumption and catchment scenarios, which showed a potential for water savings between 85% and 100% of the total current hospital consumption, with different reservoir sizes, and a maximum volume of up to 13.420 m³ per year. Therefore, according to the infrastructure availability in the HU, the components of the system to be implemented and their cost were determined, in such a way that in relation to the current water supply rate of the public network, the project technical viability was evaluated through the financial indicators: net present value, internal rate of return and period for return on investment. Concluding that it is a viable project for its implementation in the HU, being possible to obtain a drinking water economy of 7,660 m³ per year for current non-potable uses, and up to 12,300 m³ per year for non-potable uses, at the end of projected occupation of the HU, with a reserve size of 40 m³. Finding a return on investment of less than 10 years, and positive financial indicators in a period of analysis of 20 years. Finally, the water potential saving was analyzed with the implementation of actions to reduce water consumption in the building and the potential achieved with the use of rainwater on its own, and the union of the two procedures. Being estimated a water potential saving of up to71% of the water consumption and of 39% of the consumption projected at the end of its constructions.
Keywords: Aproveitamento de águas pluviais; Potencial de economia de água potável; Edificações mais sustentáveis; Conservação da água em estabelecimentos de saúde; Aprovechamiento de aguas pluviales; Potencial de ahorro de agua potable; Edificaciones más sustentables; Conservación del agua en establecimientos de salud; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDROLOGIA